2016
DOI: 10.1016/j.chroma.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and experimental study of enzyme and reactant mixing in capillary electrophoresis based on-line methods

Abstract: The establishment of an efficient reaction mixture represents a crucial part of capillary electrophoresis based on-line enzymatic assays. For ketamine N-demethylation to norketamine mediated by the cytochrome P450 3A4 enzyme, mixing of enzyme and reactants in the incubation buffer at physiological pH was studied by computer simulation. A dynamic electrophoretic simulator that encompasses Taylor-Aris diffusivity which accounts for dispersion due to the parabolic flow profile associated with pressure driven flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 30 publications
(33 reference statements)
2
27
0
Order By: Relevance
“…Separation of ketamine and norketamine enantiomers was achieved anionically using highly sulfated γ‐cyclodextrin (HS‐γ‐CD) as chiral selector. In the previous work, the 1D dynamic electrophoresis simulator GENTRANS , extended to include Taylor–Aris diffusivity to account for transverse diffusion associated with pressure‐driven plug injection , was employed to characterize mixing occurring during plug insertion and short application of voltage . In the present communication, a first simulation approach of the electrophoretic processes that take place after incubation, including the enantiomeric separation of the analytes ketamine and norketamine, is reported.…”
Section: Input Parameters For Simulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Separation of ketamine and norketamine enantiomers was achieved anionically using highly sulfated γ‐cyclodextrin (HS‐γ‐CD) as chiral selector. In the previous work, the 1D dynamic electrophoresis simulator GENTRANS , extended to include Taylor–Aris diffusivity to account for transverse diffusion associated with pressure‐driven plug injection , was employed to characterize mixing occurring during plug insertion and short application of voltage . In the present communication, a first simulation approach of the electrophoretic processes that take place after incubation, including the enantiomeric separation of the analytes ketamine and norketamine, is reported.…”
Section: Input Parameters For Simulationsmentioning
confidence: 99%
“…The steps in a typical online assay are as follows: (1) consecutive hydrodynamic injection and mixing of enzyme and reactant solution plugs, (2) incubation of the reaction mixture, (3) voltage application and separation, and (4) detection of the reaction products. Two different CE‐based online assays were developed in our laboratory for monitoring the enantioselective N ‐demethylation of ketamine to norketamine, which is mediated by the cytochrome P450 3A4 (CYP3A4) enzyme. Separation of ketamine and norketamine enantiomers was achieved anionically using highly sulfated γ‐cyclodextrin (HS‐γ‐CD) as chiral selector.…”
Section: Input Parameters For Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 To develop electromagnetophoretic applications more extensively to various microscale systems, it will be crucially important to investigate in detail the phenomena of the electromagnetophoretic convection of the medium. Any study of the convection of a liquid in micro-systems will have a more important meaning as a novel technique of micro-mixing, since it has been widely studied as a bottle-neck technique in μTAS, 11 lab-on-a-chip, 12,13 capillary systems, [14][15][16] and many microchannel methods. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Some reviews have also been reported concerning effective mixing in microchannels 34,35 and in small-scale production.…”
Section: Introductionmentioning
confidence: 99%